2009
DOI: 10.1093/nar/gkp816
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide modifications in three functionally important regions of the Saccharomyces cerevisiae ribosome affect translation accuracy

Abstract: Important regions of rRNA are rich in nucleotide modifications that can have strong effects on ribosome biogenesis and translation efficiency. Here, we examine the influence of pseudouridylation and 2′-O-methylation on translation accuracy in yeast, by deleting the corresponding guide snoRNAs. The regions analyzed were: the decoding centre (eight modifications), and two intersubunit bridge domains—the A-site finger and Helix 69 (six and five modifications). Results show that a number of modifications influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 53 publications
2
101
0
1
Order By: Relevance
“…It has been previously observed that rRNA modifications can influence translational fidelity. We used dual reporter vectors (Baudin-Baillieu et al 2009) to determine whether the lack of methylations in H70 and H71 of 25S rRNA affect programmed frame shifting or stop codon recognition. In the rcm1Δsnr75Δsnr13Δ strain the read-through of the UAA and UGA termination codons was significantly increased ∼1.6-fold and 2.4-fold, respectively.…”
Section: Rcm1 (Ynl022c) Methylates the Cytosine 2278 In 25s Rrnamentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously observed that rRNA modifications can influence translational fidelity. We used dual reporter vectors (Baudin-Baillieu et al 2009) to determine whether the lack of methylations in H70 and H71 of 25S rRNA affect programmed frame shifting or stop codon recognition. In the rcm1Δsnr75Δsnr13Δ strain the read-through of the UAA and UGA termination codons was significantly increased ∼1.6-fold and 2.4-fold, respectively.…”
Section: Rcm1 (Ynl022c) Methylates the Cytosine 2278 In 25s Rrnamentioning
confidence: 99%
“…However, to date only a handful of studies demonstrating the importance of rRNA modifications for correct ribosome function have been reported. For example, a cluster of pseudouridines in the A-site finger of the large ribosomal subunit in yeast positively affects translation efficiency and fidelity (PieknaPrzybylska et al 2008;Baudin-Baillieu et al 2009). Also, simultaneous removal of several modifications in the 18S rRNA decoding center results in lower amino acid incorporation rates, reduced translational fidelity, and delayed 18S rRNA synthesis (Baudin-Baillieu et al 2009;Liang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few special members, including U3 and U14, small nucleolar RNAs are required for pre-rRNA processing and ribosome assembly. One of the most abundant modifications in rRNAs, 2′-O-methylated nucleotides cluster in functionally important regions and are believed to fine-tune ribosome structure and function (8)(9)(10)(11).Box C/D RNAs have a bipartite structure and contain the C (RUGAUGA; R is a purine) and D (CUGA) box motifs at two ends and the related C′ and D′ box motifs in the internal regions. Each pair of boxes C and D combine into a characteristic kink turn (K-turn) or K-loop structure (12-15).…”
mentioning
confidence: 99%
“…A few special members, including U3 and U14, small nucleolar RNAs are required for pre-rRNA processing and ribosome assembly. One of the most abundant modifications in rRNAs, 2′-O-methylated nucleotides cluster in functionally important regions and are believed to fine-tune ribosome structure and function (8)(9)(10)(11).…”
mentioning
confidence: 99%